Mucus plugging, air trapping, and bronchiectasis are important outcome measures in assessing progressive childhood cystic fibrosis lung disease. Issue 4 (21st January 2020) - Robinson, Terry E.; Goris, Michael L.; Moss, Richard B.; Tian, Lu; Kan, Peiyi; Yilma, Mignote; McCoy, Karen S.; Newman, Beverley; de Jong, Pim A.; Long, Frederick R.; Brody, Alan S.; Behrje, Rhett; et al.
Abstract: Objective: To determine which outcome measures could detect early progression of disease in school‐age children with mild cystic fibrosis (CF) lung disease over a two‐year time interval utilizing chest computed tomography (CT) scores, quantitative CT air trapping (QAT), and spirometric measurements. Methods: Thirty‐six school‐age children with mild CF lung disease (median [interquartile range] age 12 [3.7] years; percent predicted forced expiratory volume in 1 second (ppFEV1 ) 99 [12.5]) were evaluated by serial spirometer‐controlled chest CT scans and spirometry at baseline, 3‐month, 1‐ and 2‐years. Results: No significant changes were noted at 3‐month for any variable except for decreased ppFEV1 . Mucus plugging score (MPS) and QATA1 and A2 increased at 1‐ and 2‐years. The bronchiectasis score (BS), and total score (TS) were increased at 2‐year. All variables tested with the exception of bronchial wall thickness score, parenchymal score (PS), and ppFEV1, were consistent with longitudinal worsening of lung disease. Multivariate analysis revealed baseline PS, baseline TS, and 1‐year changes in BS and air trapping score were predictive of 2‐year changes in BS. Conclusions: MPS and QATA1‐A2 were the most sensitive indicators of progressive childhood CF lung disease. The 1‐year change in the bronchiectasis score had the most positive predictive power for 2‐year change in bronchiectasis.